Characterization Of Fretting Fatigue of 7075-T6 Aluminium Alloy - Jacob, M. Suresh Devanesan (2006)
The main aim of the research work is to present theoretical and experimental approaches to the problem of fretting fatigue using 7075-T6 aluminum alloy as a specimen and En24 steel as a pad. A literature review is carried out to explain the contact mechanics of complete contact configuration for the fretting fatigue loading condition. The literature review includes fretting fatigue crack initiation, crack propagation and failure mechanisms and concludes with the different fretting fatigue test facilities. A novel fretting fatigue test rig has been designed to measure and control the critical parameters: normal load, frictional force and relative displacement at the contact interface using a data acquisition facility. The crack initiation and propagation data also recorded during the experiments to ascertain the crack behavior. The fretting fatigue tests have been carried for the three cyclic axial stresses 290 MPa, 300 MPa and 325 MPa with normal stress 45 MPa, 60 MPa, 90 MPa. During the experiments the frictional force, Q is measured and plotted with the number of cycles. The frictional force response increases rapidly during initial stage of experiments and attains a steady state condition approximately after 100 cycles and dwells there until the specimen fails. The frictional force versus axial load hysterias loops for different cycles are drawn which shows that the contact zone experiences partial slip regime. The Coulomb law is applied to determine the coefficient of friction which shows that higher coefficient of friction is observed for the lower normal stress and decreases gradually with an increases in normal stress. The crack propagation with dl/dN and Ak, growth curves shows that considerable retardation in crack growth is observed for the higher normal stress of 90 MPa with the three axial stresses which are caused by crack closure due to high compressive normal load. The experimental observation of fretting fatigue life results shows that increase in normal stress reduces the crack initiation cycles as well as the total life to failure for that constant axial stress. The fatigue life reduces by an average factor of 7.34, 12.46 and 17.48 respectively for the axial stress of 290 MPa with the normal stress of 45 MPa, 60 MPa and 90 MPa. The similar behaviour is observed for the other combinations fretting fatigue loading condition. A theoretical model is developed using the asymptotic analysis to study the equivalence of stress state at the pad edge for the complete contact of dissimilar materials with Dundurs parameters a,p and at the root of the notch based on the order of stress singularity, (A-1). The strain energy density criterion is applied to predict the crack initiation angle using the order of stress singularity, (A-1). The crack initiation angle compares well with the experimental angle values, which is obtained through the scanning electron microscope. A fretting fatigue life prediction model is developed based on the strain energy density criterion in which a critical process zone size is used to estimate crack initiation life and crack analogue model is used to determine the crack propagation life. The critical process zone size is estimated using the notch analogy for the fretting fatigue loading condition. The theoretically calculated crack initiation and propagation lives compares well with the experimental results.